Struktur simbolik tari topeng Patih pada Dramatari wayang topeng Malang di Dusun Kedungmonggo - Mintarto, Soerjo Wido (citeus, 2010)
Dramatari Wayang Topeng Malang reflects the life style of the Malangese. They are believed to have historical relevance with the development Malang s oldest culture which was under the reign of Kanjuruhan Kingdom around 7th century. Topeng Patih dance, the opening dance of the traditional theatre performance are closely related to the pattern of the show related to the space, time, and content. So the symbolic structuralist theoretical approach would be the chosen strategy to understand the symbolic internal meanings. The analysis indicates that the choreographic structure of Tari Topeng Patih consists of 7 elements: character, ritual, communication, body movement, make up and wardrobe art, instrument, and stage for the performance. All of them are oriented towards the grandeur of refined character or attitude.